Andrographolide protects against cigarette smoke‐induced oxidative lung injury via augmentation of Nrf2 activity. (12th March 2013) - Guan, SP; Tee, W; Ng, DSW; Chan, TK; Peh, HY; Ho, WE; Cheng, C; Mak, JC; Wong, WSF
<x xml:space="preserve">Abstract</x> Background and Purpose Cigarette smoke is a major cause for chronic obstructive pulmonary disease (COPD). Andrographolide is an active biomolecule isolated from the plant Andrographis paniculata. Andrographolide has been shown to activate nuclear factor erythroid‐2‐related factor 2 (Nrf2), a redox‐sensitive antioxidant transcription factor. As Nrf2 activity is reduced in COPD, we hypothesize that andrographolide may have therapeutic value for COPD. Experimental Approach Andrographolide was given i.p. to BALB/c mice daily 2 h before 4% cigarette smoke exposure for 1 h over five consecutive days. Bronchoalveolar lavage fluid and lungs were collected for analyses of cytokines, oxidative damage markers and antioxidant activities. BEAS‐2B bronchial epithelial cells were exposed to cigarette smoke extract (CSE) and used to study the antioxidant mechanism of action of andrographolide. Key Results Andrographolide suppressed cigarette smoke‐induced increases in lavage fluid cell counts; levels of IL‐1β, MCP‐1, IP‐10 and KC; and levels of oxidative biomarkers 8‐isoprostane, 8‐OHdG and 3‐nitrotyrosine in a dose‐dependent manner. Andrographolide promoted inductions of glutathione peroxidase (GPx) and glutathione reductase (GR) activities in lungs from cigarette smoke‐exposed mice. In BEAS‐2B cells, andrographolide markedly increased nuclear Nrf2 accumulation, promoted binding to antioxidant response element (ARE) and total cellular glutathione level in response to CSE. Andrographolide up‐regulated ARE‐regulated gene targets including glutamate‐cysteine ligase catalytic (GCLC) subunit, GCL modifier (GCLM) subunit, GPx, GR and heme oxygenase‐1 in BEAS‐2B cells in response to CSE. Conclusions Andrographolide possesses antioxidative properties against cigarette smoke‐induced lung injury probably via augmentation of Nrf2 activity and may have therapeutic potential for treating COPD.